Information-revelation and coordination using cheap talk in a game with two-sided private information - Chirantan Ganguly; Indrajit Ray (Cardiff University, Cardiff Business School, 2015)
We consider a Bayesian game, namely the Battle of the Sexes with private information, in which each player has two types, High and Low. We allow cheap talk regarding players' types before the game and prove that the unique fully revealing symmetric cheap talk equilibrium exists for a low range of prior probability of the High-type. This equilibrium has a desirable type-coordination property: it fully coordinates on the ex-post efficient pure Nash equilibrium when the players' types are different. Type-coordination is also obtained in a partially revealing equilibrium in which only the High-type is not truthful, for a medium range of prior probability of the High-type.
Keywords: C72; 330; Battle of the Sexes; Private Information; Cheap Talk; Coordination; Full Revelation